Barriers to physical activity in women with and without breast cancer - Gomes, Maria Laura Brizio; Pinto, Stephanie Santana; Domingues, Marlos Rodrigues (ABCS Health Sciences, 2020)
Introduction: Regular physical activity (PA) is important for the entire population, equally for healthy people and survivors of breast cancer. Despite the benefits of PA, there are women who do not attain the recommendation from the World Health Organization (WHO). Objective: To describe and compare the barriers to PA in women with and without breast cancer. Methods: A cross-sectional descriptive study was performed. The consisted of 230 women with primary breast cancer diagnosed up to one year and 231 women without breast cancer. Both groups were matched by age (±5 years). The participants answered a questionnaire with questions about barriers to PA and sociodemographic, anthropometric and behavioral characteristics. Results: Women with breast cancer perceived more barriers to PA than those without diagnosis (59.4% versus 40.7%). The barriers most cited by women diagnosed with breast cancer were “feeling discomfort or pain” (59.6%) and “feeling tired” (56.1%). The barriers most mentioned by women without diagnosis were “lack of money” (21.6%) and “lack of company” (19.1%). Conclusion: Women with breast cancer report more barriers than women without the disease. Therefore, it is suggested that they have a lower level of PA in leisure time. The perceived barriers to PA among women with and without breast cancer are similar, but they differ in the physical barriers.